2002
DOI: 10.1638/1042-7260(2002)033[0263:hbdirp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperostotic Bone Disease in Red Pandas (Ailurus Fulgens)

Abstract: Three adult red pandas (Ailurus fulgens) developed multiple periarticular exostoses in their elbow joints. Two of these animals also had extensive periosteal new bone formation and osteosclerosis of the ulnae and radii and mild periosteal new bone deposition on the femurs. One animal also showed extensive hyperostosis of the cranium and mandibles. Dietary concentrations of calcium and phosphorus were estimated to be adequate, but dietary vitamin A and D appeared excessive when compared with recommended levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In comparison, skeletal changes such as vertebral hyperostosis due to hypervitaminosis A have been described for the domestic cat (Corbee et al, 2014). For other Carnivora such as the red panda, periarticular exostoses due to presumed hypervitaminosis A have also been published (Lynch & Slocombe, 2002). Any basic feed for giant anteaters and tamanduas should, therefore, be evaluated very critically for vitamins A and D content.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, skeletal changes such as vertebral hyperostosis due to hypervitaminosis A have been described for the domestic cat (Corbee et al, 2014). For other Carnivora such as the red panda, periarticular exostoses due to presumed hypervitaminosis A have also been published (Lynch & Slocombe, 2002). Any basic feed for giant anteaters and tamanduas should, therefore, be evaluated very critically for vitamins A and D content.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this distinction is no longer relevant to the general science of living organisms. It has even been argued, by most philosophers of medicine (14,19,32,87), with the notable exception of Christopher Boorse and some of his followers (10,46), that this distinction is not grounded in hard science but merely reflects our values.…”
Section: Physiology As the Science Of Physiological And Pathological mentioning
confidence: 99%